Art therapy in museums and galleries : reframing practice - Coles, Ali; Jury, Helen (Jessica Kingsley Publishers, 2020)
This edited collection explores creative uses of museums and galleries for art therapy. It includes international examples of work with a variety of client groups and range of institutions. Chapters discuss the benefits of these spaces for therapeutic work, as well as the skills and theoretical frames required for working in these settings.